Corporate Social Responsibility: Community Empowerment as a part of Conservation and Management Program In Sangiran world Heritage Site - Rudito, Bambang (SBM ITB, 2008)
This article writes about how to give solution to corporate for applying community development program especially in program area, competency impact from the program for the company and also help the government to solve cost problem for maintaining the historical site for keeping archaeological site as national identity and world heritage of human history. This article, also writes about method and way out or solution to increase people prosperity through the changing of people cultural value that have already absorbed in their behavior by using community need. This is a result of the research in Sangiran the archaeological site where is founded some bones of ancient artifacts such as Pithecanthropus erectus, Homo erectus, the Java man. It used social mapping and ethnographic approach for collecting data through the community.Keywords: Corporate social responsibility, community empowerment, Sangiran